CALCULATION OF RESISTANCE AND ENGINE POWER OF PURSE SEINE FISHING BOATS IN TAKALAR REGENCY USING MAXSURF SOFTWARE - Amran, Andi Ana Humaerah; Ghaffar, Mukhlisa A.; Erna, Erna (Universitas Mataram, 2025)
The main factor in determining the power of a ship's main engine is the ship's resistance resulting from the shape of the ship's hull. Calculation of ship resistance can be done using software, namely Maxsurf Resistance, which can simulate the shape of a ship's hull under water. This research aims to determine the total resistance of a purse seine fishing vessel and the power required to move a 30 GT vessel. The design made from this ship model is then analyze to calculate the ship's resistance a nd the required engine power. The ship resistance calculation method uses the Holtrop method. This method is used because the hull of a 30 GT ship is a V-shaped model. From the results of the discussion, it is concluded that ship resistance can be seen from several speed variations produced by looking at the service speed of 30 GT fishing boats in the Takalar Regency area. From this research, the resistance value for speeds of 0-6 knots resulted in a resistance value of 1.4 kN and engine power of 5,861 hp. Then there is a significant need for engine power or power which occurs from a speed of 7 knots to 10 knots because the value of the ship's resistance continues to increase in line with the speed of the ship. At the maximum speed of a 30 GT purse seine fishing vessel of 10 knots, the total resistance of the vessel is 7.4 kN and the engine power required is 50.572 H.